The Use of MATLAB Programming to Compare Experimental vs Modeled PEMFCs using the Nernst and Butler-Volmer’s Equation-Based Mathematical Models - Bishwash Paneru; Biplov Paneru; Nitish Pandey; Kabita Neupne; Pukar Adhikari; Ramhari Poudyal (Universitas Komputer Indonesia, 2025)
This study evaluates Proton Exchange Membrane Fuel Cell (PEMFC) efficiency using mathematical models based on the Nernst and Butler-Volmer equations. Developed in MATLAB, these models simulated output current utilizing experimental parameters temperature, pressure, and reactant concentrations across varying external resistances. Comparing the simulated outcomes with experimental data revealed significant discrepancies, including negative current values in the models. These deviations stem from the limited operational parameters incorporated in the simulation. The sensitivity analysis further confirmed that PEMFC performance is heavily dependent on multiple variables. Consequently, the findings demonstrate that an accurate mathematical model for PEMFCs necessitates integrating a broader range of influencing parameters to reliably predict practical performance